2016
DOI: 10.1007/s11573-016-0840-6
|View full text |Cite
|
Sign up to set email alerts
|

Does umbrella branding really work? Investigating cross-category brand loyalty

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…First, our empirical setting is limited to a single multi‐product firm. It thus does not include actions of competitors, which have been considered to be associated with customers' cross‐category brand loyalty and purchase behavior (e.g., the share of category requirements; Grasby et al, 2022; Silberhorn et al, 2017). Second, to enhance the efficacy of our findings, future research needs to incorporate data from diverse industry settings other than just retail (e.g., Evanschitzky et al, 2017; Shah et al, 2012) and additional demographic or geographic characteristics associated with customers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, our empirical setting is limited to a single multi‐product firm. It thus does not include actions of competitors, which have been considered to be associated with customers' cross‐category brand loyalty and purchase behavior (e.g., the share of category requirements; Grasby et al, 2022; Silberhorn et al, 2017). Second, to enhance the efficacy of our findings, future research needs to incorporate data from diverse industry settings other than just retail (e.g., Evanschitzky et al, 2017; Shah et al, 2012) and additional demographic or geographic characteristics associated with customers.…”
Section: Discussionmentioning
confidence: 99%
“…As such, brand‐related factors such as advertising (Balachander & Ghose, 2003), brand logos (Han et al, 2010), and brand heritage (Pecot et al, 2018) act as signals for enhanced quality associated with the parent brand, resulting in customers' commitment to a brand and repeat purchase behavior. Further, the brand signals that both existing and future products under the same brand will also meet customer expectations, that is, brand‐quality expectations (Aaker & Keller, 1990; Silberhorn et al, 2017). Therefore, when making decisions about a new product, customers use their prior experience with the brand to reduce their perceived risk, especially when quality information is missing or not fully employed (Erdem & Chang, 2012; Sebri & Zaccour, 2017).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Bennett et al (2000) found buyers of both leaded and unleaded petrol were more likely to purchase the same brand across both categories. Finally, Silberhorn et al (2017) found consumers who are loyal to a brand in one category have a higher probability of being loyal to the brand extension for nine non-food categories.…”
Section: Cross Category Purchasingmentioning
confidence: 90%